Rancang Bangun Robot Smart Farming Berbasis Computer Numerical Control (Sensor dan Monitoring) - Ilham Eka Putra; Wiwin Styorini (ABEC Indonesia, 2021)
Urban farming is an activity of farming in urban areas by using the yard area or corners of the house efficiently. The obstacle is the urban community who spend a lot of time working outside. Therefore, tools are needed to do watering, planting seeds, and monitoring plants based on the internet of things. The main objective of this research is to create a sophisticated agricultural system with IOT applications, it can easily maintain the farm, this robot which will later be named Robot Smart Farming (SF-BOT). SF-BOT has options for planting seeds, measuring soil moisture and watering. To implement this feature, SF-BOT works from the Soil Moisture Sensor reading with the help of Arduino and Raspberry pi. In addition SF-BOT can also be to plant seeds and show monitoring and can make streaming video in realtime.SF-BOT is controlled via webserver interface to select a menu of vegetables to be planted and select the point of planting. In addition, it can also display sensor monitoring and video streaming. The results of the DHT sensor accuration of 98,69 % and magnetic sensor accuration of 100%. The measurement results can be displayed and can be monitored from the webserver. Keywords: SF-BOT, Soil Moisture, Arduino, Raspberry pi, Internet of Things